Analisis Mengenai Bagaimana Pemerintah Daerah Terlibat dan Merancang Strategi Untuk Mengurangi Penyalahgunaan Narkotika di Kalangan Remaja - Lydia Natalia Amul; Maulia Yuniar Safitri; Lia Ferina (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Narcotics abuse among teenagers is a serious problem that affects the health and future of the younger generation. Local governments play an important role in efforts to prevent and control this phenomenon. This study aims to analyze the involvement of local governments and the strategies they have designed to reduce drug involvement among teenagers. Through a look at implemented policies and programs, this research explores various approaches used by local governments to mitigate the negative impacts of narcotics protection and increase awareness and education in the community.